DOP39 Safety of combination biologic and anti-rejection therapy post-liver transplantation in patients with inflammatory bowel disease: London Ontario experience. (25th January 2019) - Al Draiweesh, S; Ma, C; Alkhattabi, M; Chande, N; Feagan, B G; Gregor, J C; Khanna, R; Marotta, P; Sandhu, A; Qumosani, K; Teriaky, A; Brahmania, M; et al.
Abstract: Background: Despite anti-rejection immunosuppressive therapies post-liver transplantation (LT), patients with concurrent inflammatory bowel disease (IBD) may have persistent bowel inflammation that requires addition of biologic therapy. The aim of this study was to evaluate the safety of combination biologic and anti-rejection therapy in IBD patients after LT. Methods: The LT Registry at London Health Sciences Centre (LHSC) was searched to identify all patients undergoing LT from 1985 to 2018. IBD patients initiated on biologic treatment post-LT, in addition to anti-rejection therapy, were eligible for inclusion. Medical chart review was conducted to extract safety outcomes, including rates of infections, malignancy, colectomy and death. Results: Nineteen patients were included (78.9% male, mean age 46.0 years, 8 patients with ulcerative colitis), followed for a median duration of 19 months (IQR 5.8, 30.8). Indications for LT included: primary sclerosing cholangitis (PSC) (14/19, 73.7%), autoimmune hepatitis (AIH) (2/19, 10.5%), AIH-PSC overlap syndrome (2/19, 10.5%), and biliary atresia (1/19, 5.3%). Post-LT, six patients were treated with only TNF antagonists (infliximab in 5 patients, golimumab in 1 patient); eight patients with only anti-integrin therapies (vedolizumab in 7 patients, natalizumab in 1 patient); and five patients with sequential TNF antagonists followed by either ustekinumab ( n = 2) or vedolizumab ( n = 3). Six patients required long-term prednisone. The most commonly used anti-rejection therapies were tacrolimus and mycophenolate mofetil. Disease course was complicated by infections in nine patients (47.4%), most commonly Clostridium difficile colitis (4/19, 31.6%). One patient had recurrent C. difficile infection and one patient had CMV colitis and viremia. Other infections included cholangitis ( n = 2), perianal abscess ( n = 1), JC virus seroconversion but without progressive multifocal leukoencephalopathy ( n = 1) and hospital-acquired pneumonia ( n = 1). Two patients required colectomy for refractory colitis. One patient required re-transplantation due to PSC recurrence. No deaths or malignancies were reported although one patient developed low-grade colonic dysplasia. Conclusions: This is the largest reported case series from a single centre to date evaluating the safety of combination biologic therapy with anti-rejection regimens in IBD patients post-LT. Whilst there appeared to be an increased risk of enteric infections, especially C. difficile, there were no life-threatening infections reported. Active screening for enteric infections should be pursued in these patients presenting with increased IBD symptoms.